Blood Collection Agency Messaging to Donors and the Public in Canada and Australia During the Early Days of COVID-19 - Haw, Jennie; Thorpe, Rachel; Holloway, Kelly (Frontiers in Communication, 2022)
COVID-19 has posed unprecedented challenges to health systems around the world, including blood collection agencies (BCAs). Many countries, such as Canada and Australia, that rely on non-remunerated voluntary donors saw an initial drop in donors in the early days of the pandemic followed by a return to sufficient levels of the blood supply. BCA messaging plays a key role in communicating the needs of the blood operator, promoting and encouraging donation, educating, and connecting with the public and donors. This paper is an interpretive discourse analysis of BCA messaging in Canada and Australia from March 1-July 31, 2020 to understand how BCAs constructed donation to encourage donation during this period and what this can tell us about public trust and blood operators. Drawing on multiple sources of online content and print media, our analysis identified four dominant messages during the study period: 1) blood donation is safe; 2) blood donation is designated an essential activity; 3) blood is needed; and 4) blood donation is a response to the pandemic. In Canada and Australia, our analysis suggests that: 1) in a time of uncertainty, donors and some publics trusted the BCA to be an organization with expertise to ensure that donation is safe, essential, and able to meet patient needs; and 2) BCAs demonstrated their trustworthiness by aligning their messaging with public health and scientific experts. For BCAs, our analysis supports donor communications that are transparent and responsive to public concerns and the local context to support public trust. Beyond BCAs, health organizations and leaders cannot underestimate the importance of building and maintaining public trust as countries continue to struggle with containment of the virus and encourage vaccine uptake.